Зерно з Меджибожа - Горбаненко, С.А.; Толкачов, Ю.І. (Археологія і давня історія України, 2019)
Подано палеоетноботанічні матеріали з розкопок Меджибожа. За результатами ідентифікаційного аналізу встановлено, що обгорілі зерна
переважно належать житу. Проаналізовано роль
цього злаку, запропоновано ймовірні місця, де могли бути житні поля неподалік місця знахідки. During the archaeological research of the Medjybizh fortress (fig. 1), palaeoethnobotanical materials were
found three times in its yard: in 1991, 2013 and 2015. The first definition was made by G. O. Pashkevich.
Mostly rye was identified as well as bromus, sorrel and an ergot fungus claviceps purpurea. From materials
ща 2015 about 30 ml of grain were provided, mostly rye, which is approximately 1800—2000 grains. This
is a sample of the harvest of one year. Single kernels of hulled barley (5); emmer (2) and soft wheat (1) were
identified. Weeds are represented by 3 species, they are convolvulus (19), brome grasses (11) and cleavers (7)
(figs. 2—4). Identified weeds are concomitant for cultivated cereals
and real anthropochores; they may be useful for therapeutic purposes. Brome grass is a winter plant
that pollutes crops of winter rye and wheat. Fields pollution indicates a use of old arable fields:
the population lived in this place continuously from the eleventh century. Consequently, the fields exploded
about 2—3 centuries. Winter crops also show the use of old arable fields. According to the aggregate of weeds,
these fields were located on high places with droughty soils. According to the analysis of topography and soil,
these fields were in the western sector on the elevated plateau (supposedly the places of Dolzhok and Pereimska Dacha).
Find of the rye also indirectly indicates a high level of development of agriculture. While plowing tools from
Medzhybizh are unknown, we should assume the use of plow, which is the most progressive form of them.